Flavonoid Composition and Antioxidant Activity of Tragia volubilis L. Methanolic Extract - Juan Carlos Romero-Benavides; Nora Cecilia Atiencie-Valarezo; Rodrigo Duarte-Casar (Plants, 2023)
Several species from the genus Tragia L. in the family Euphorbiaceae are part of the ethnomedicine of traditional cultures, and have a variety of uses. Tragia volubilis L. is a species spread through tropical America and Africa with several ethnomedical uses, particularly for wound healing and reproductive issues. In this study, we assess the phytochemical composition and antioxidant activity of the methanolic extract of the aerial parts of T. volubilis collected in southern Ecuador. The phytochemical screening of the extract shows the preliminary presence of carbohydrates, alkaloids, flavonoids, and tannins. The extract shows an Antioxidant Activity Index of 1.14, interpreted as strong antioxidant activity. Four flavonoid compounds were isolated through chromatographic procedures and identified through NMR spectroscopy: avicularin, quercitrin, afzelin, and amentoflavone. The biological activity of these compounds matches the ethnopharmacological uses of the species. This is the first phytochemical study of T. volubilis and supports its traditional medicinal uses.